2015
DOI: 10.1007/s10897-015-9897-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Telephone vs. In‐Person BRCA1/BRCA2 Genetic Counseling

Abstract: Telephone genetic counseling (TC) for hereditary breast/ovarian cancer risk has been associated with positive outcomes in high risk women. However, little is known about how patients perceive TC. As part of a randomized trial of TC versus usual care (UC; in-person genetic counseling), we compared high risk women’s perceptions of: (1) overall satisfaction with genetic counseling; (2) convenience; (3) attentiveness during the session; (4) counselor effectiveness in providing support; and (5) counselor ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 49 publications
4
71
0
Order By: Relevance
“…However, contrary findings that the GC delivery model was not associated with satisfaction in GC in general for women with a BRCA1/2 mutation have been reported. [25] Participants felt that they did not receive information about the importance of the GC from the health-care professionals, in accordance with previous findings that health-care professionals can play an important role in helping women with breast cancer decide whether or not to have GC. [26,27] Our participants also mentioned that they received inadequate written material, in line with findings that most women with breast or ovarian cancer were inadequately prepared because of lack of pre-information.…”
Section: Discussionsupporting
confidence: 86%
“…However, contrary findings that the GC delivery model was not associated with satisfaction in GC in general for women with a BRCA1/2 mutation have been reported. [25] Participants felt that they did not receive information about the importance of the GC from the health-care professionals, in accordance with previous findings that health-care professionals can play an important role in helping women with breast cancer decide whether or not to have GC. [26,27] Our participants also mentioned that they received inadequate written material, in line with findings that most women with breast or ovarian cancer were inadequately prepared because of lack of pre-information.…”
Section: Discussionsupporting
confidence: 86%
“…First, genetic counselor session ratings did not differ between TC and UC. This finding, in conjunction with other results from this trial [19, 21], suggests that TC and UC may be comparable in terms of how counselors perceive their ability to deliver key aspects of genetic counseling. Second, genetic counselors rated their sessions with non-Hispanic White participants as slightly more effective than their sessions with minority participants.…”
Section: Discussionsupporting
confidence: 78%
“…As reported previously [19], we assessed patient perceptions of their pre-test genetic counseling session at the 2-week follow-up interview via face-valid Likert-style measures. Specifically, we assessed patients’ perceptions of: 1) Satisfaction with the session (Not at all satisfied to very satisfied); 2) Convenience of the genetic counseling process (Extremely inconvenient to extremely convenient); 3) Ability to maintain attention during the session (Extremely difficult to not difficult); 4) Counselor provision of emotional support (Extremely ineffective to extremely effective); and 5) Counselor’s ability to recognize participant emotions (Extremely ineffective to extremely effective).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The provider should also acknowledge the increased complexity of panel testing for many genes. In the absence of a local cancer genetics professional, early research has shown the efficacy of genetic counseling via telephone conversation [44][45][46][47][48] and telemedicine via live videoconferencing [49]. Other service delivery models discussed among the summit attendees included group counseling instead of individual counseling and online counseling in real time or by previously prepared materials.…”
Section: Delivery Care Modelsmentioning
confidence: 99%